A Comparison of Service-oriented, Resource-oriented, and Object-oriented Architecture Styles - Thelin, Jorgen (2003)
The three common software architecture styles commonly used in distributed systems and XML Web Services are compared and contrasted. In particular, the key differences between traditional SOAP and REST styles are explored. Guidelines are presented on which style is most applicable for certain application scenarios, and when a combination of styles is necessary.